Manhaj Abi Bakr Ibn al-'Arabi fi ikhtiyaratihi al-fiqhiyah min khilal kitabihi "'Aridat al-ahwadhi" : kitab al-taharah namudhajan = Abu Bakr ibn al-`Arabi's methodology for juristic opinions in his book 'Aridat al-ahwadhi, using "The book of purification" as a data sample / Qusay ibn Muhammad Karyim - Muhammad Karyim, Qusay (2010)
This thesis explains Abu Bakr ibn al-‘Arabi’s juristic choices in “The Book of Purification” from his work ‘Aridat al-Ahwadhi, and his methodology for doing so. This researcher has used an inductive methodology, surveying the works of Ibn al-‘Arabi as well as other books, particularly books of fiqh and usul al-fiqh, and then analyzing Ibn al-‘Arabi’s choices and comparing them with the legal opinions of other jurists. The study also undertakes a concise biography of Ibn al-‘Arabi and an overview of his book ‘Aridat al-Ahwadhi and the general methodology he employed in it. After that it focuses on extracting his fiqh opinions from “The Book of Purification”, studying them and comparing them with the legal opinions of other jurists from his own school of thought, the Maliki madhhab, as well as those of jurists from other madhhabs. It then explains his methodology for making those choices and his methods of expressing them. The results of the study are that Ibn al-‘Arabi has made more than ١٣٠ choices [as to the weightiest of variant opinions] on fiqh issues in “The Book of Purification” and that he relies on the various sources of the Shari‘ah in doing so, such as the Qur’an and Sunnah, consensus (ijma‘) the practice of the Sahabah, and other classes of evidence. He uses a variety of ways to express his preferences, sometimes explicitly stating them and sometimes not. He frequently gives preference to the opinions of his school of thought, the Maliki madhhab, but he also frequently opposes them (in approximately one quarter of the issues). He also takes an independent stance on a number of issues. All of that is based upon his ijtihad and his interpretation of the relevant evidence, as is treated in detail in the thesis. This indicates that he was, indeed, a mujtahid, a jurist qualified to reason independently in fiqh issues. Mujtahids of this caliber would operate within the evidentiary methodology (usul) of a particular well established madhhab but were distinguished by their independent stances on detailed fiqh issues. This was only because of their vast knowledge and sophisticated understanding.